Sistem Absensi Karyawan Berbasis Web pada Robotics Education Center Harapan Indah - Franky; Jullend Gatc (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Robotics Education Center is a company engaged in education that aims to improve the mechanical and motor skills of children. In the management of absence, Robotics Education Center employees have problems in managing attendance data. Robotics Education Center requires a long process in processing attendance data in and out so that errors occur in making reports. Therefore a new system was made to make it easier to do attendance data processing, to reduce data input errors on the report. The web-based system includes employee data, position data, and employee attendance data. The researcher developed the system using the SDLC method and the Prototype model. The results of this study are the employee attendance system that can be used by the Harapan Indah Robotics Education Center, and has been tested using black box testing to find out the functions of the system can run as expected.